Obtaining molybdenum-99 in the IRT-T research reactor using resonance neutrons; Nuclear Instruments and Methods in Physics Research. Sec. B: Beam Interactions with Materials and Atoms; Vol. 213 - Ryabchikov A. I. Aleksandr Ilyich; Skuridin V. S.; Nesterov E. V.; Chibisov E. V.; Golovkov V. M. (2004, 2004)
The yield of 99Mo from the 98Mo(n,γ)99Mo reaction significantly depends of the energy spectrum of the neutron flux. It is well known that the cross-section for this reaction is about 130 mb, whereas the resonance integral of the reaction is 6.9 b. The aim of this work was to investigate the conditions that let to increase 99Mo yield from the targets with natural and enriched isotope composition under irradiation by resonance neutrons at the IRT-T research reactor.The calculations of integrated cross-sections of all Mo isotopes in the region of the 98Mo resonances showed that screening in the target with natural isotope composition by other isotopes is relatively small. So the 98Mo in the natural mixture can be activated by resonance neutrons approximately in the same manner as pure 98Mo.Experimental measurements of the 98Mo(n,γ) effective cross-section using the MoO3 sample with natural and enriched composition in the reactor channels with the beryllium moderator with the thickness of 20 up to 90 mm showed that the effective cross-sections in these channels reach the value of 700 mb. The contribution of the epithermal neutrons into the 98Mo activity was 68% for the enriched targets and 78% for natural molybdenum, respectively.At that channel it is possible to produce 99Mo with specific activity up to 3.4 Cu/g with samples of natural isotope composition and up to 15 Cu/g with enriched samples on the base of reactors with neutron flux of (1.7 × 1014 n/(cm2 s)). Such 99Mo specific activity is enough not only to realize extraction technologies production of 99mTc, but to manufacture sorption generators of 99mTc without wastes.